Forming new health behavior habits during weight loss maintenance—The PREVIEW study. - Gareth Stratton (Health Psychology, 2022)
Changing lifestyle habits to achieve and maintain weight loss can be effective in prevention of type 2 diabetes. Ability to resist temptations is considered one of the key factors in behaviour change. This study examined how both habit-strength, motivation, and temptations for an energy-dense diet developed during the maintenance stage of a behaviour modification intervention tool. Participants with prediabetes and overweight/obesity were recruited in the two-phase trial PREVIEW with the aim to achieve ≥8% body weight loss over 2 months, and maintain weight loss over a subsequent 34-month period. The four-stage intervention (PREMIT) supported participants in weight-maintenance. Uni- and multivariate analyses were completed from the beginning of the PREMIT maintenance stage (week 26 of the PREVIEW trial) with 962 individuals who completed the trial. Habit-strength and ability to resist temptations increased during the early PREMIT adherence stage (weeks 26 to 52) before plateauing during middle (weeks 52 to 104) and late (weeks 104 to 156) PREMIT adherence stages. Higher habit-strength for energy dense diet was significantly associated with larger weight-regain (p ≤ .007). No changes in motivation or interaction with PREMIT attendance were observed. Changing diet habits is a complex, multifactorial process with participants struggling at least with some aspects of weight maintenance. Habits against consuming energy dense, sweet and fatty, food appeared effective in protecting against weight re-gain. The observed effect sizes were small reflecting the complexity of breaking old habits and forming new ones to support long term maintenance of weight loss.